Identification of lanthanum‐specific peptides for future recycling of rare earth elements from compact fluorescent lamps. Issue 5 (21st March 2017) - Lederer, Franziska L.; Curtis, Susan B.; Bachmann, Stefanie; Dunbar, W.Scott; MacGillivray, Ross T.A.
ABSTRACT: As components of electronic scrap, rare earth minerals are an interesting but little used source of raw materials that are highly important for the recycling industry. Currently, there exists no cost‐efficient technology to separate rare earth minerals from an electronic scrap mixture. In this study, phage surface display has been used as a key method to develop peptides with high specificity for particular inorganic targets in electronic scrap. Lanthanum phosphate doped with cerium and terbium as part of the fluorescent phosphors of spent compact fluorescent lamps (CFL) was used as a target material of economic interest to test the suitability of the phage display method to the separation of rare earth minerals. One random pVIII phage library was screened for peptide sequences that bind specifically to the fluorescent phosphor LaPO4 :Ce 3+, Tb 3+ (LAP). The library contained at least 100 binding pVIII peptides per phage particle with a diversity of 1 × 10 9 different phage per library. After three rounds of enrichment, a phage clone containing the surface peptide loop RCQYPLCS was found to bind specifically to LAP. Specificity and affinity of the identified phage bound peptide was confirmed by using binding and competition assays, immunofluorescence assays, and zeta potential measurements. Binding and immunofluorescence assays identified the peptide's affinity for the fluorescent phosphor components CAT (CeMgAl11 O19 :Tb 3+ ) and BAM (BaMgAl10 O17 :Eu 2+ ). No affinity was found for other fluorescent phosphor components such as YOX (Y2 O3 :Eu 3+ ). The binding specificity of the RCQYPLCS peptide loop was improved 3–51‐fold by using alanine scanning mutagenesis. The identification of peptides with high specificity and affinity for special components in the fluorescent phosphor in CFLs provides a potentially new strategic approach to rare earth recycling. Biotechnol. Bioeng. 2017;114: 1016–1024. © 2016 Wiley Periodicals, Inc. Abstract : Recycling of rare earth elements that are part of electronic scrap is difficult due to their low abundance and their similar physical and chemical characteristics. Lederer and co‐workers used phage display to identify highly specific peptides for LaPO4 :Ce, Tb; a green fluorescent phosphor of compact light bulbs. Mineral selectivity was demonstrated by binding studies, immunochemistry and zeta potential determination. When combined with bio‐flotation, these peptides that discriminate between different phosphors may allow the first efficient recycling process for rare earth elements.